2008
DOI: 10.1302/0301-620x.90b8.20390
|View full text |Cite
|
Sign up to set email alerts
|

Femoral impaction bone allografting with an Exeter cemented collarless, polished, tapered stem in revision hip replacement

Abstract: Femoral impaction bone allografting has been developed as a means of restoring bone stock in revision total hip replacement. We report the results of 75 consecutive patients (75 hips) with a mean age of 68 years (35 to 87) who underwent impaction grafting using the Exeter collarless, polished, tapered femoral stem between 1992 and 1998. The mean follow-up period was 10.5 years (6.3 to 14.1). The median pre-operative bone defect score was 3 (interquartile range (IQR) 2 to 3) using the Endo-Klinik classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
5
36
0
2
Order By: Relevance
“…Schreurs et al reported 33 patients with 33 hips followed for an average of 10.4 years with a 100% survival for aseptic loosening and 85% for any reason [20]. Wraighte and Howard reported 75 patients with 75 hips also followed for over 10 years with 92% survival at 10.5 years [27]. Sierra et al reported 40 patients all treated with longer stems with a 90% survival at 10 years [23] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schreurs et al reported 33 patients with 33 hips followed for an average of 10.4 years with a 100% survival for aseptic loosening and 85% for any reason [20]. Wraighte and Howard reported 75 patients with 75 hips also followed for over 10 years with 92% survival at 10.5 years [27]. Sierra et al reported 40 patients all treated with longer stems with a 90% survival at 10 years [23] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment has been described using extensively coated femoral stems [3,13,26], modular stems with distal tapers [10,12,14,15,17,19,22], and impaction bone grafting with cemented polished stems [4,7,16,21,23,25,27]. Femoral impaction grafting, first reported by Gie et al in 1993 [5], has the advantage of adding bone to the deficient femur, but it is a time-consuming procedure with reported risks of fracture ranging from 5% to 12% [1,5,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although modularity has potential benefits, fracture at the modular junction and corrosion reactions present challenging complications [6]. Other potential revision options that have shown favorable outcomes in younger and elderly populations with Type III defects include impaction grafting and impaction grafting with cementation [34,35,38]. Good outcomes (improved pain and function) with acceptable complication rates also can be achieved in Type III defects with proximal femoral replacement [16,27,31].…”
Section: Descriptionmentioning
confidence: 99%
“…Paprosky Type IV defects are those with severe metaphyseal and diaphyseal bone loss, typically with severe ectasia (pronounced expansion of endosteal bone with profound cortical thinning) of the femoral canal making uncemented fixation unreliable. Reconstruction options usually are limited to proximal femoral replacements, impaction grafting with a cemented stem, and allograft prostheses composites [16,27,31,34,35,38].…”
Section: Descriptionmentioning
confidence: 99%